2022
DOI: 10.3390/en15041254
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Magnetic Nanoparticle Enhanced Microwave Pyrolysis for Oily Sludge

Abstract: In view of the high dielectric constant of magnetic nanoparticles, this paper intends to use it as a new type of microwave absorbing medium to accelerate the microwave pyrolysis process of oily sludge. Microwave thermogravimetric reaction and pyrolysis product staged collection devices were established, respectively. The main stage of pyrolysis process of oily sludge was divided based on the thermogravimetric experiments. Mechanism was studied through the characteristics of pyrolysis products and reaction kine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…The method of photocatalytic oxidation has become the most widespread due to the availability of reagents, high efficiency, environmental friendliness and relatively low energy consumption compared to other physico-chemical methods. Among the NCS for photooxidation are TiO 2 , ZnO, ZrO [34][35][36]. In a number of processes related to the heterogeneous photocatalytic purification of water and soil from organic pollutants, NCs from the mentioned list are also used [15,17,[21][22][23]25,31,32].…”
Section: Nanocatalysts and Nanocomposites In Pretreatment Processes F...mentioning
confidence: 99%
See 1 more Smart Citation
“…The method of photocatalytic oxidation has become the most widespread due to the availability of reagents, high efficiency, environmental friendliness and relatively low energy consumption compared to other physico-chemical methods. Among the NCS for photooxidation are TiO 2 , ZnO, ZrO [34][35][36]. In a number of processes related to the heterogeneous photocatalytic purification of water and soil from organic pollutants, NCs from the mentioned list are also used [15,17,[21][22][23]25,31,32].…”
Section: Nanocatalysts and Nanocomposites In Pretreatment Processes F...mentioning
confidence: 99%
“…Among the processes that differed from AOPs, pyrolysis is known as an approach to the destruction of organic pollutants using NCs [34]. The successful decomposition of oily sludge by ZnFe 2 O 4 (NPs = 30 nm) during three-stage pyrolysis with the activation of NCs by microwaves was shown.…”
Section: Nanocatalysts and Nanocomposites In Pretreatment Processes F...mentioning
confidence: 99%
“…The addition of magnetic ZnFe2O4 will improve the efficiency of the pyrolysis process. It shows that the content of C 4-C12 increased by 3.5%, and the content of C18 + decreased by 4.1%, and this shows that magnetic nanoparticles have good catalytic [7]. The purpose of this study is to determine the optimal size of raw materials and microwave power in the manufacture of liquid smoke using the microwave-assisted pyrolysis method…”
Section: Introductionmentioning
confidence: 98%
“…This combination was conducive to accelerating the degradation of asphaltene. Qi et al 5 analyzed the main pyrolysis stages of oily sludge by thermogravimetric experiments. The mechanism of magnetic nanoparticles for enhancing the effect of the microwave pyrolysis of oily sludge was studied, and it was found that magnetic ZnFe 2 O 4 particles could improve the pyrolysis efficiency.…”
Section: Introductionmentioning
confidence: 99%